Hazard identification, risk assessment, and determining control (HIRADC) pada kegiatan maintenance underground decline di tambang bawah tanah - Melati, Vita Mardhiyanti; Djunaidi, Zulkifli (Holistik Jurnal Kesehatan, 2026)
Background: Underground declines are the primary access point for the movement of heavy equipment, personnel, and utilities, and pose operational complexity and high safety risks due to interactions between activities in the underground environment. The high potential for hazards in maintenance activities involving vehicle traffic, ventilation systems, and drainage management requires the implementation of a systematic prevention strategy using the Hazard Identification, Risk Assessment, and Determining Control (HIRADC) method. Purpose: To apply HIRADC to underground decline maintenance activities in underground mines, thereby identifying hazards, assessing risks, and determining controls for safe work. Method: This study used a qualitative descriptive approach through observations and interviews of underground decline maintenance activities with one supervisor, one underground manager, and one geotechnical personnel from December 2025 to February 2026. The study covered the HIRADC stages, from consultation and communication, risk context determination, hazard identification and risk assessment, risk control, to monitoring and review. Primary data was obtained from observations of underground technical activities and secondary data from internal company documents. The analysis was conducted using a risk matrix based on the multiplication of likelihood and consequence in accordance with ISO 31000:2018 principles and an occupational safety risk assessment approach. Results: The application of HIRADC to underground decline maintenance activities identified seven primary hazards: working at height, rock support failure, waterlogging, electrical energy, fire, hazardous atmospheres, and interactions between heavy equipment, light vehicles, and workers. The risk assessment results using a 5x5 matrix showed all risk levels were in the moderate category after the implementation of existing controls, indicating that the combination of engineering, administrative, and PPE controls reduced the risk to an acceptable level. Conclusion: All hazards in underground decline maintenance activities were at a moderate risk level, indicating that existing controls were able to maintain risk within acceptable limits and support safe and controlled work execution.   Keywords: Hazard Identification, Risk Assessment, and Determining Control (HIRADC); Underground Decline Maintenance; Underground Mining.   Pendahuluan: Underground decline merupakan akses utama bagi pergerakan alat berat, personel, dan utilitas yang memiliki kompleksitas operasional serta risiko keselamatan tinggi akibat interaksi antar aktivitas di lingkungan bawah tanah. Tingginya potensi bahaya pada kegiatan maintenance yang melibatkan lalu lintas kendaraan, sistem ventilasi, dan pengelolaan drainase menuntut penerapan strategi pencegahan sistematis melalui metode Hazard Identification, Risk Assessment and Determining Control (HIRADC). Tujuan: Untuk menerapkan HIRADC pada kegiatan maintenance underground decline di tambang bawah tanah, sehingga dapat mengidentifikasi bahaya, menilai risiko, dan menentukan pengendalian agar pekerjaan dapat dilakukan secara aman. Metode: Penelitian ini menggunakan pendekatan deskriptif kualitatif melalui observasi dan wawancara pada kegiatan maintenance underground decline dengan subjek satu pengawas, satu manajer underground, dan satu personel geotechnical selama periode Desember 2025 hingga Februari 2026. Penelitian mencakup tahapan HIRADC mulai dari konsultasi dan komunikasi, penentuan konteks risiko, identifikasi bahaya dan penilaian risiko, pengendalian risiko, hingga pemantauan dan peninjauan, dengan data primer dari pengamatan aktivitas teknis underground dan data sekunder dari dokumen internal perusahaan. Analisis dilakukan menggunakan matriks risiko berdasarkan perkalian likelihood dan consequence sesuai prinsip ISO 31000:2018 dan pendekatan penilaian risiko keselamatan kerja. Hasil: Penerapan HIRADC pada kegiatan maintenance underground decline mengidentifikasi tujuh sumber bahaya utama yaitu bekerja di ketinggian, kegagalan penyanggaan batuan, genangan air, energi listrik, kebakaran, atmosfer berbahaya, serta interaksi alat berat, kendaraan ringan, dan pekerja. Hasil penilaian risiko menggunakan matriks 5×5 menunjukkan seluruh tingkat risiko berada pada kategori sedang (moderate) setelah penerapan pengendalian yang ada, yang mengindikasikan bahwa kombinasi pengendalian rekayasa teknik, administratif, dan APD mampu menurunkan risiko hingga batas yang dapat diterima. Simpulan: Seluruh sumber bahaya pada kegiatan maintenance underground decline berada pada tingkat risiko sedang (moderate) yang menunjukkan bahwa pengendalian yang ada mampu menjaga risiko dalam batas yang dapat diterima serta mendukung pelaksanaan pekerjaan secara aman dan terkendali.   Kata Kunci: Hazard Identification, Risk Assessment, and Determining Control (HIRADC); Maintenance Underground Decline; Tambang Bawah Tanah.